Most Earth-surface calcites precipitate out of isotopic equilibrium - M. Daëron (Nature Portfolio, 2019)
Isotopic thermometry of carbonate minerals postulates that their composition reflects thermodynamic equilibrium constants. Here the authors constrain equilibrium relationships between temperature, 18O/16O and clumped isotopes and find that most natural calcites form out of isotopic equilibrium.